Hambatan Komunikasi Terapeutik antara Perawat dan Keluarga Pasien di Ruang Intensive Care - Rieke Kartika Winata; Popon Haryeti; Ayu Prameswari Kusuma Astuti (JURNAL BIDANG ILMU KESEHATAN, 2026)
Therapeutic communication is an important aspect in nursing practice, especially in the Intensive Care Unit, which is synonymous with critical conditions, high workloads, and complex information needs of patient families. Communication barriers can arise from physical/environmental, psychological, individual-social, and semantic factors, potentially leading to miscommunication, decreased family satisfaction, and reduced service effectiveness. This study aims to describe the barriers to therapeutic communication between nurses and patient families in the Intensive Care Unit. This study used a quantitative descriptive method with a population of 52 ICU and NICU nurses through a total sampling technique. The research instrument used was the Nurse-Patient Communication Barriers questionnaire that had been modified according to the research context. The results of the study indicate that the overall picture of barriers to therapeutic communication is in the moderate category. Of the total of 52 nurses, 48 nurses (92.4%) experienced communication barriers in the moderate category, while 4 nurses (7.6%) were in the low category, and none reported high barriers. This study provides a systematic overview of barriers to therapeutic communication in intensive care units and strengthens the application of Joseph A. DeVito's communication theory, as well as providing a basis for developing effective communication strategies to improve the quality of nursing services.